2023
DOI: 10.1177/09697764231162229
|View full text |Cite
|
Sign up to set email alerts
|

Energy poverty in the Energy Community region: Interrogating policy formulation and coverage

Abstract: The capacity of the state to develop and implement policy at the complex nexus of energy infrastructure, social inequality and housing is indicative of the political priorities of governing structures and, by extension, the nature of statecraft more generally. We compare and contrast the energy poverty amelioration policies of two former Yugoslav and two post-Soviet states located outside the European Union, but seeking to join its regulatory sphere – Serbia, Montenegro, Ukraine and Georgia – against the backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Baker et al show similar results [6]. Consequently, Bouzarovski et al compared policies for decreasing energy poverty in former post-communist countries outside the EU, while their research found that the majority of the states in the analyzed region did not make enough solutions for solving basic problems, which connects with the improvement of living quality, energy efficiency, and gender inequality [7]. However, energy poverty is present in the politics of all countries.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Baker et al show similar results [6]. Consequently, Bouzarovski et al compared policies for decreasing energy poverty in former post-communist countries outside the EU, while their research found that the majority of the states in the analyzed region did not make enough solutions for solving basic problems, which connects with the improvement of living quality, energy efficiency, and gender inequality [7]. However, energy poverty is present in the politics of all countries.…”
Section: Literature Reviewmentioning
confidence: 93%
“…2 efficiency, and gender inequality [7]. However, energy poverty is present in the politics of all countries.…”
Section: Introductionmentioning
confidence: 99%
“…Affolderbach and O'Neill (2024) examine the use of green buildings to explore the coming Ecology, economy and climate crisis in European urban and regional development 1243211E UR0010.1177/09697764241243211European Urban and Regional StudiesEditorial editorial2024 Editorial together of perspectives on materialities, discourses and 'lived sustainabilities'. Finally, Bouzarovski et al (2024) focus on energy poverty amelioration policies in four east European states to address the intersection of housing quality, energy efficiency and gender inequality.…”
mentioning
confidence: 99%